Learning about learning: a cybernetic model of skill acquisition. Issue 9 (28th October 2014) - Scott, Bernard; Bansal, Abhinav
Abstract : Purpose: – The purpose of this paper is to explain some phenomena observed in the acquisition of motor skills: the loss of conscious access to knowledge of the structure of a skill and the awareness that an error has been made prior to the receipt of knowledge of results. Although there are rich descriptive accounts of skill acquisition in the literature, there are no satisfactory explanatory models of the cognitive processes involved. The paper provides such a model. Design/methodology/approach: – In the 1970s, the first author implemented a computer program model of the cognitive processes involved in learning and skill acquisition, based on a series of empirical investigations. Recently, with assistance from the second author, the model has been reviewed, updated and re-implemented. The paper sets this work in the broader context of a theory of learning and teaching, conversation theory. Findings: – The model provides a constructivist account of skill acquisition and associated phenomena. The model provides theoretical foundations for conversation theory. Practical implications: – The model adds to the understanding of motor skill acquisition and to the understanding of processes of learning and teaching in general. Originality/value: – The model and its interpretation are an original contribution to the skills acquisition literature.